2020
DOI: 10.1186/s13075-020-02249-1
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of BAFF receptor, BR3, on monocytes correlates with B cell activation and clinical features of patients with primary Sjögren’s syndrome

Abstract: Background: We reported that the production of BAFF (B cell-activating factor) and IL-6, both of which are involved in survival and differentiation of B cells, is dysregulated in monocytes of patients with primary Sjögren's syndrome (pSS). In this study, we investigate the relationship between possible aberrations of pSS monocytes and clinical features of pSS patients and the contribution of monocytes to B cell activation, a mechanism involved in the pathogenesis of pSS. Methods: Expression of BAFF-receptor (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Recent studies have proven the existence of distinct monocyte subsets and they have critical roles in the development of some rheumatic diseases such as SLE and rheumatoid arthritis (RA), and targeting monocytes is a potential treatment for those diseases (17,33). There are also some studies focusing on the roles of monocytes in SjS, and some have shown that aberrant changes in immunophenotypes, intracellular functional pathways and epigenetics exist in SjS patients (20)(21)(22)(23)(24). Those outcomes suggest the key roles of monocytes in the development and progression of SjS, though the underlying mechanisms are largely elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have proven the existence of distinct monocyte subsets and they have critical roles in the development of some rheumatic diseases such as SLE and rheumatoid arthritis (RA), and targeting monocytes is a potential treatment for those diseases (17,33). There are also some studies focusing on the roles of monocytes in SjS, and some have shown that aberrant changes in immunophenotypes, intracellular functional pathways and epigenetics exist in SjS patients (20)(21)(22)(23)(24). Those outcomes suggest the key roles of monocytes in the development and progression of SjS, though the underlying mechanisms are largely elusive.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, monocytes can participate in the pathogenesis of SLE by immune mechanisms such as secreting pro-inflammatory cytokines and assisting in the activation of B cells and T cells (16)(17)(18)(19). In recent years, the roles of monocytes in the pathogenesis of SjS have also gained increased attentions, and some studies have proved possible key roles of monocytes in the development and progression of SjS (20)(21)(22)(23)(24). However, the mechanisms of monocytes in SjS have not been fully clarified, and further research is required.…”
Section: Introductionmentioning
confidence: 99%
“…We validated the increase of BAFF mRNA and protein in multiple senescent models ( Figures 1 and Figure 1—figure supplement 1 ) and found that IRF1 transcriptionally elevated BAFF mRNA levels in senescence ( Figures 2 and Figure 2—figure supplement 1 ). Given that BAFF is mainly produced by monocytes (Yoshimoto et al 2011; Yoshimoto et al 2020), we focused on the induction of BAFF in the monocytic cell line THP-1. Transcriptomic and proteomic analyses suggested a role for BAFF in monocyte activation and inflammation in senescence ( Figures 3 and Figure 3— figure supplement 1 ), as BAFF depletion led to a striking reduction in the production of SASP factors in irradiated THP-1 cells, while BAFF overexpression or ectopic addition of BAFF increased the secretion of pro-inflammatory molecules ( Figures 4 and Figure 4—figure supplement 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, symptom variables might not be objective parameters associated with the pathogenic mechanism of pSS. Subclassification of patients with pSS has focused on molecular signatures that appear to be more associated with pathogenesis of the disease [ 2 , 12 15 ]. James et al found that transcriptional modules identified three clusters with differences in interferon, inflammation modules, and molecules, such as CXCL10, CXCL9, and BAFF [ 16 ].…”
Section: Discussionmentioning
confidence: 99%